LIFE VALUES ​​IN MYTHOLOGICAL DRAMAS IN KANNADA - Bharati sangappa Gaddi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
A mythological drama is a drama based on the stories, characters and events in the Puranas. It generally reflects religious, moral and cultural values ​​and shows the audience an ideal way of life.